Beyond the microscope: integrating inclusion, diversity, equity, and accessibility principles in immunology education through the IDE-A rubric - Claudette P. Davis; Erika Lorenzana Del Villar; Sumali Pandey; Ekaterini Papadopoulou; Zemirah Ngow; Cynthia A. Wenner (Frontiers in Education)
Textbooks are essential resources for developing immunological literacy. This article emphasizes expanding educational focus beyond traditional technical content to more broadly encompass inclusion and equity in the classroom. Equitable and inclusive teaching requires thoughtful selection of course materials by applying principles of inclusion, diversity, equity, and accessibility (IDE-A), yet clear guidance using these principles for course design, especially in textbook selection, is limited. To address this gap, the authors developed and tested the IDE-A rubric and assessed a sample of immunology textbooks, widely used at both undergraduate and graduate levels, to evaluate the rubric’s utility. Each textbook was rated on the overall commitment to the principles of the IDE-A framework, assessing the extent to which the textbook authors and publishers make a concerted effort to address these principles in the introduction, preface, and/or overall framing of the content. Inclusion and diversity were evaluated by examining evidence of stereotype threat, including the use of names in case studies and questions, the selection of textbook imagery, and how diverse representations, perspectives, and voices were acknowledged and incorporated into descriptions of concepts and historical context. Equity and accessibility were assessed by evaluating availability of textbooks and ancillary materials at no cost or reduced price, availability of multiple textbook formats, and publisher’s provision of accessible versions. Furthermore, the rubric could help instructors maintain diversity within STEM fields. This study is one of the first structured evaluations that apply IDE-A principles in textbook selection, demonstrating how looking “beyond the microscope” creates more inclusive learning environments.